The Monitoring Environmental noise in Coffee Production, CCT/NCBA Companies in Bidau Lesidere Villige, Dili District Dili City Timor Leste - Anibal Idalino Loe (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Noise-induced hearing loss is hearing loss caused by exposure to quite loud noise over a long period of time and is usually caused by noise in the work environment, in this case the company environment. Working environment noise is a major problem in occupational health which is a standard of OSH in various companies, the relationship between excessive noise exposure and hearing loss has been known since ancient times. Various epidemiological studies of noise-induced hearing loss have explored the relationship or risk factors between work, exposure to noise levels and the degree of hearing loss. The purpose of this study was to determine and survey the noise of electronic machines on hearing loss. The research method used is a quantitative, observational method using a cross observational study design.